Nauczyciel – uczący się dorosły. Refleksje nauczycieli wychowania przedszkolnego pracujących w oparciu o program Tablit - Basińska, Anna (Nauczyciel wczesnej edukacji: Rozwijanie kompetencji zawodowych, 2016)
In this paper, a problem of teachers’ learning and making changes in their teaching is undertaken as well as results of an evaluation survey carried out among teachers who were testing Tablit – innovative kindergarten curriculum for two years are presented. The curriculum required a lot of changes in teacher’s organization of educational process, methods of teaching and understanding the teaching and learning processes of young pupils. Teachers received a lot of support during the implementation of the program, which were to help them in the implementation of the changes.